The Concept Of Property Ownership In The Perspective Of Ibn Taimiyah - Iffah Febri anti Fitriyatul Lailiyah; Muhammad Latoif Ghozali (Jurnal Ilmiah Ekonomi Islam, 2023)
In life without us realizing in the life of a human being will not be separated in terms of muamalah which activity is concerned with needs. The concept of ownership is crucial in economics. This field of ownership is not only related to economic aspects but also social and political aspects, so ownership is an important position of microeconomic theory in Islamic economics as well as capitalist economics. The research design used is a literature study. research conducted to examine data by studying, understanding, and examining theories or assumptions in relevant materials or literature sources. The research methodology uses qualitative research methodology. The purpose of this method is to explain what happened and Discovering generalizations requires investigation, recording, analysis, and interpretation of previous events. In property rights i.e. individual property rights (milkiyyat al-fardiyyah), common property (milkiyyat al-ammah), state ownership (milkiyyat al-daulah). The picture above illustrates to us, namely Ibn Taimiyyah's view of the privileges of property in Islam, defining property rights as the authority to use an object based on sharia, such as guaranteeing ownership of abandoned land so that it can be cultivated, inherited, traded. Since this will later be accounted for before God, then return everything to the rules that come from giving the mandate that is God, how to obtain it and how to use it. Keywords : Possession, property, Ibn Taimiyah